Educational ecotourism as a medium for environmental character building: Lessons from a honey-picking experience - Wahyu Surakusumah; Halisa; Abdul Faqih Fajar Sidik; Chersa Steffany Polandos (Journal of Character and Environment, 2026)
Background: This study aims to analyze the feasibility of honeybee cultivation attractions as an object for developing educational ecotourism and to formulate strategies for developing the “Honey Picking” educational tourism package Taman Hutan Raya Ir. H. Djuanda, Bandung. Methods: This research employed a descriptive method with a qualitative approach. Primary data were obtained through observation, in-depth interviews, and questionnaires distributed to visitors using purposive sampling, while secondary data were gathered from literature reviews and relevant supporting documents. Data analysis was carried out using the SWOT method to identify internal and external factors influencing the development of the tourism package. Findings: The results show that the honey-picking educational ecotourism program has strong internal strengths and favorable external conditions, with IFAS and EFAS scores of 3.03 and 2.89, placing it in Quadrant I. Interactive educational activities, natural attractions, accessibility, and community support drive growth, while improvements in digital promotion, management capacity, and safety standards are required to ensure sustainable development. Conclusion: The study concludes that the “Honey Picking” educational ecotourism package holds strong potential to be developed as a sustainable conservation-based educational tourism model. This activity not only increases visitors’ knowledge and environmental awareness but also provides economic and social benefits for local communities and supports biodiversity conservation efforts in the Taman Hutan Raya Ir. H. Djuanda Grand Forest Park area, Bandung. Novelty/Originality of this article: The novelty of this study lies in its development of an interactive “Honey Picking” edu-ecotourism concept based on honeybee cultivation, which has not previously been explored in the context of Taman Hutan Raya Ir. H. Djuanda. Additionally, the study offers a strategic, data-driven framework using SWOT analysis to guide the creation of sustainable conservation-based educational tourism packages.